(3QSGdI aj GdCSeGA GdJj dG JfUQas - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3HNW GdeDdas)
(3ChdgG (B:s
(3hGdMeO ddg hGdUdGI hGdSdGe Ydi QShd bhdg(B: (3hCeG GdaJMI aJchf YdGeI ddNaV aj GdGSe GdPj dG jfUQa hGYde Cfg GNJda aj GTJbGbg gd gh ef GdUQa hgh GdNGdU ef GddH hGdefUQa NGdU ef THg GdaYd hGdMQa Ch ef GdUQja hgh GdUhJ dCf GdUQa hgh GdJfhjf UhJs
(3BNQgG (B:s
(3hGSJYeGdg cCSeGA GdCaYGd hGaJbGQg cGdehUhdGJ hGdeJecf bSeGf eJecf Cecf hgh GdefUQa heJecf ZjQ Cecf hgh GdPj dG jfUQa dTHg GdaYd aj chfg aQYG ef LgJjf eNJdaJjf hef LgI Jbhe ebGe LgJjfs
(3LGA aj fgGjI GdQSGdI Cf GdeDda Cfgi GdQSGdI SfI (B1268(3g` bGd(B: (3hfMf CSQi HeOjfI CfHhGQ YfO GdaQfSjjf OeQge Gddg Bejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdUQas